2019
DOI: 10.1177/0734016819846223
|View full text |Cite
|
Sign up to set email alerts
|

Police Officer and Supervisor Perceptions of Body-Worn Cameras Pre- and Postimplementation: The Importance of Officer Buy-in

Abstract: Body-worn cameras (BWCs) are increasingly more common in their use among police officers. Research on BWCs is the focus of an increasing number of studies seeking information on stakeholder perceptions and the impact of the technology on behavior and other related outcomes. Although the emerging research is mixed, several studies find that officers have concerns about the use of BWCs and may not fully support their use. The current study utilizes survey data from two Southern police departments. Police officer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…A final attitude subcategory revolved around the issue of police supervision, particularly their use of the videos to monitor an officer's performance. Several studies reported that officers believed that video evidence would be used against them (Adams and Mastracci, 2019a;Newell and Greidanus, 2017;Owens and Finn, 2018;Snyder et al, 2019). One study found that officers became "risk-averse," writing more traffic tickets to reduce questions about their decision-making (Ready and Young, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A final attitude subcategory revolved around the issue of police supervision, particularly their use of the videos to monitor an officer's performance. Several studies reported that officers believed that video evidence would be used against them (Adams and Mastracci, 2019a;Newell and Greidanus, 2017;Owens and Finn, 2018;Snyder et al, 2019). One study found that officers became "risk-averse," writing more traffic tickets to reduce questions about their decision-making (Ready and Young, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some research found that officers viewed cameras as a tool that can reduce their use of force (Smith, 2019) or protect them from illegitimate complaints (Fallik et al, 2018;Pelfrey and Kenner, 2018). Other research indicated that some officers changed their views of BWC, usually for the better, once exposed to their utility (Clare et al, 2019;Snyder et al, 2019;White et al, 2018). Others have argued, however, that officers' acceptance of BWCs requires a multidimensional assessment to uncover the nuance and complexity of police officers' subjective thinking toward this technology (Fallik et al, 2018;Kyle and White, 2017;Lum et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lum et al (2019) identify at least 32 articles investigating officer attitudes toward BWCs, up from 13 studies reviewed four years earlier (Lum et al 2015). The officer-attitude literature consistently finds that as officers gain experience with BWCs, their perceptions become more positive despite early skepticism and negativity (Fouche 2014;Gaub et al 2016;Jennings, Fridell, and Lynch 2014;Snyder, Crow, and Smykla 2019;Todak and Gaub 2019;White, Todak, and Gaub 2018). Officers may find BWCs useful in public complaint and internal affairs investigations (Fouche 2014;Goetschel and Peha 2017;Owens and Finn 2017;Pelfrey and Keener 2016), evidence collection (Gaub, Todak, and White 2018;White et al 2018), and improving job performance (Gramagila and Phillips 2017).…”
Section: Body-worn Camera Researchmentioning
confidence: 99%
“…In addition, officers’ compliance with processes and policies governing the use of BWCs will also likely be related to their attitudes toward BWCs and the benefits they perceive of this technology (Gaub et al, 2016). As a result, it is imperative to the success of a BWC program that corrective service agencies and prison management understand how correctional officers view the use of this technology and their willingness to use BWCs as part of their role (Gaub et al, 2016; Snyder et al, 2019). Better understanding the concerns of officers can also help to “shed light on specific issues that officers may have leading to suggestions for how departments can assuage these issues and eventually lead to an easier transition” (Snyder et al, 2019, p. 4).…”
Section: Prior Researchmentioning
confidence: 99%